PENGARUH PENGGUNAAN APLIKASI WORDWALL TERHADAP PEMAHAMAN KONSEP BANGUN DATAR SISWA KELAS V SD MUHAMMADIYAH PERUMNAS - Tasyah, Hamdani; Andi Husniati; Andi Alim Syahri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using the Wordwall application in improving the understanding of fifth-grade students at SD Muhammadiyah Perumnas regarding the concept of plane geometry. The research employed a quantitative pre-experimental approach with a one-group pre-test and post-test design involving 20 students. Data analysis was conducted using a paired sample t-test and N-gain score calculation. The results showed that the average pre-test score of 25.70 increased significantly to 88.45 in the post-test. The paired sample t-test indicated a significance value of 0.000, which is lower than 0.05, meaning that there is a significant difference between the results before and after the treatment.